Synthesis of Functionalized Spirooxindole Polycycles: Use of Cyclic 1,3-Diones as Reactants or as Condition-Tuning Molecules - Sohail, Muhammad; Tanaka, Fujie (Synlett, 2023)
This account describes the strategies for the synthesis of functionalized spirooxindole polycycles, including enantiomerically enriched forms, that we have developed and reported. The syntheses of these complex molecules were accomplished in a few steps starting from relatively simple oxindole derivatives and other reactants. Organocatalytic reactions involved in kinetic resolution or in dynamic kinetic transformation led to the formation of products with high diastereo- and/or enantioselectivities. Cyclic 1,3-diones, such as 1,3-cyclohexanedione, were used as reactants to provide two reaction sites for the construction of polycyclic ring systems. To tune the reaction conditions, 2-methyl-1,3-cyclohexanedione was employed. The developed methods enabled the synthesis of complex functionalized spirooxindole polycycles bearing up to seven stereogenic centers, and will be useful for the synthesis of potentially bioactive molecules.1 Introduction2 Formal (4+1) Cycloaddition and Enantioselective Michael/Henry Cascade Reactions3 Dynamic Stereoselective Aldol/Oxacyclization Cascade Reactions4 Dynamic Kinetic Asymmetric Transformation: Diastereo- and Enantioconvergent Michael/Henry Reactions5 Dimerization Reactions6 Conclusion
Keywords: asymmetric catalysis; annulation; cycloadditions; enantioselectivity; Michael addition; organocatalysis